Erythrocytes of Little Ground Squirrels Undergo Reversible Oxidative Stress During Arousal From Hibernation - Klichkhanov, Nisred K.; Nikitina, Elena R.; Shihamirova, Zainab M.; Astaeva, Maria D.; Chalabov, Shamil I.; Krivchenko, Aleksandr I. (Frontiers in Physiology, 2021)
The hibernation of small mammals is characterized by long torpor bouts alternating with short periods of arousal. During arousal, due to a significant increase in oxygen consumption, tissue perfusion, and the launch of thermogenesis in cells, a large amount of reactive oxygen species (ROS) and nitrogen (RNS) can be formed, which can trigger oxidative stress in cells. To estimate this possibility, we studied the intensity of free-radical processes in the red blood cells (RBCs) of Little ground squirrels (Spermophilus pygmaeus) in the dynamics of arousal from hibernation. We found that in the torpid state, the degree of generation of ROS and RNS (8.3%, p>0.09; 20.7%, p<0.001, respectively), the degree of oxidative modification of membrane lipids and RBC proteins is at a low level (47%, p<0.001; 82.7%, p<0.001, respectively) compared to the summer control. At the same time, the activity of superoxide dismutase (SOD) and catalase (CAT) in RBC is significantly reduced (32.8%, р<0.001; 22.2%, р<0.001, respectively), but not the level of GSH. In the torpid state, SOD is activated by exogenous GSH in a concentration-dependent manner, which indicates reversible enzyme inhibition. During the arousal of ground squirrels, when the body temperature reaches 25°C, RBCs are exposed to oxidative stress. This is confirmed by the maximum increase in the level of uric acid (25.4%, р<0.001) in plasma, a marker of oxidative modification of lipids (TBARS) (82%, р˂0.001) and proteins (carbonyl groups) (499%, р˂0.001) in RBC membranes, as well as the decrease in the level of GSH (19.7%, р˂0.001) in erythrocytes relative to the torpid state and activity of SOD and CAT in erythrocytes to values at the Tb 20°C. After full recovery of body temperature, the level of GSH increases, the ratio of SOD/CAT is restored which significantly reduces the degree of oxidative damage of lipids and proteins of RBCs membranes. Thus, the oxidative stress detected at Tb 25℃ was transient and physiologically regulated.